Optimization Of The Penggerak School Program At The Educational Unit Level - Gayus Sadarman Tafonao; Sugiarto Sugiarto; Siti Rochanah (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Based on the Decree of the Minister of Education and Culture of the Republic of Indonesia No. 1177/M/2020 concerning the Penggerak School Program, the determination of the educational unit as the implementer of the Penggerak School Program is carried out by selecting the Head of the Education Unit who has learning leadership, learning that supports students and a willingness to learn that represents diversity throughout Indonesia (differentiated learning). The presence of the Penggerak School Program began with an independent curriculum development program which started from the implementation of the 2013 curriculum which was considered too rigid, the material was too dense and learning loss was caused by the impact of online learning during the Covid-19. The method used in research is libarary research methods. In general, this research describes the results of the penggerak school program carried out at the educational unit level, so that it can encourage the transformation process of educational units in order to increase student learning outcomes character in order to realize Pancasila students. Penggerak School Program has several advantages, namely being a school that can provide guidance to other schools (model school), getting assistance from expert trainers, accelerating school digitalization & improving the quality of school principals and teachers. Schools that take part in the Penggerak School Program will be expected to have output as a pioneer force in the transition to the independent curriculum.